Images of a Grandmother in the Movie â€œThe Way Homeâ€ - Ancho, Inero Valbuena; Galang, Aljon Delmo (OKARA: Jurnal Bahasa dan Sastra, 2020)
Images, as portrayed in movies, create a deep connection to its viewers, regardless of culture, history, or social status. A movie may make or break one's idea of a personality depending on role portrayal and projection. This study showcases how Filipino viewers perceive a grandmother in the movie "The Way Home". After watching the movie, participants were asked to reflect on the image of a grandmother based on the film and compare and contrast these ideas based on their personal experience and social construction of a Filipino grandmother. This study is qualitative in nature involving content analysis of perceptions of a grandmother based on a film. As Filipinos consider living with grandmothers a very meaningful experience, participants have noted very memorable childhood experiences because of this film. The Filipino society regards that those who grow up with their grandmothers, or grandparents, in general, to be more courteous, kind, and of good values. "The Way Home" may be a Korean movie but to Filipino viewers, it is a reminder that a grandmother's unconditional love is the same affection regardless of culture, history, or social status.